Clinical manifestations and diagnosis of arrhythmogenic right ventricular dysplasia in sexagenary patient - Soeiro, Alexandre de Matos; Barbosa, Rodrigo S.; Goldstein, Priscila G.; Almeida, Maria Carolina Feres de; Serrano Jr, Carlos V.; Oliveira Jr, Múcio Tavares de (Revista de Medicina, 2014)
Arrhythmogenic right ventricular dysplasia is one of the major causes of death in younger patients and its manifestations and diagnosis used to be early. In this context, diagnosis in a sexagenary patient without famylial history or previous symptoms and with possibility of correct treatment make this case unique.